ANALYSIS OF THE IMPACT OF FATHERLESS ON THE RELIGIOUS AND MORAL DEVELOPMENT OF EARLY CHILDHOOD IN TANJUNG DEAH VILLAGE - Irhamna, Irhamna; Faridy., Faizatul (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study aims to analyze the impact of fatherlessness on the religious and moral development of children in Gampong Tanjung Deah. The research method involved surveys and interviews with affected parents and children. The results indicate that fatherlessness significantly affects the religious and moral development of children in the area. Children growing up without fathers tend to struggle in acquiring strong religious understanding and moral values. The discussion encompasses factors influencing these impacts, such as social support, economic factors, and education. The conclusion highlights the importance of the father's role in shaping the religious and moral foundation of children, emphasizing the need for community support and policies to assist affected families. Without the presence of a father, children tend to lack a crucial figure in acquiring a strong understanding of religion and morals. Factors such as social support, especially from family and the community, can play a significant role in helping children overcome these difficulties. Additionally, economic aspects also influence this, as a lack of resources can hinder children's access to adequate religious and moral education. Therefore, efforts to improve social and economic support for affected families are crucial. Education also needs to be strengthened in providing religious and moral understanding to children without paternal presence. Through a deep understanding of the factors affecting the impact of fatherlessness, communities and governments can develop more effective strategies to support the religious and moral development of children in such situations.